Electro-Jet Engine: a Jet Engine without Turbine (London Journal of Engineering Research, 2026)
In accordance with efficiency criteria, the development of air transport has to the option of using large passenger airplanes, with capacities ranging from 200 to over 800 passengers and masses ranging from 100 to over 500 tons. These airplanes require a large airport infrastructure that involve major air security problems. The proposed idea is to use small, pressurized aircraft for passenger air transport, with a capacity of 4 to 9 people, including the crew, which can use small and minimally equipped airports, without complex security facilities, and can fly at altitudes of 12.000 to 18.000 m at supersonic speeds. These aircraft use Coanda-type jet engine, without a turbine, in which the compressor is driven by an electric motor, use hydrogen as fuel and are easily converted from a Coanda-type jet to a ramjet. This engine has devices for transforming thermal energy directly into electrical energy, thus generating, in whole or in part, the electrical energy necessary to drive the compressor, until the conversion of the electro-jet engine into a ramjet engine. These proposals represent a new type of jet engine nevertheless a new concept in passenger air transport. Last part studies theoretically and experimentally the conversion of thermal energy directly into electrical energy. The experimental part was based on the recovery of a part of the heat lost to the cold source, i.e. to the atmosphere, through the walls of hot part of a turboshaft jet engine. For the experimental part I used a small turboshaft jet engine installed on an ultralight helicopter. The recovery was done with a Seebeck bridge currently produced. These Seebeck bridges are manufactured in mass production, have a low maximum operating temperature compared to the temperature inside the jet engine and have a very low efficiency compared to current systems used in space technology [21], [22].